Formulation and Evaluation of Gel Containing Carbomer 940 with Combination of betel Leaf (Piper Betle L.) Extract with Gambier (Unchariagambir Roxb.) Extract Against Gram Positive Bacteria - Sharma, Devender; Saravanan, Dr. K. (Asian Journal of Pharmaceutical Research and Development, 2024)
Teethes are important parts of human body. Daily consumption of food by mouth, food stay and stick to tooth creates various problem like decay and microbial contamination on teeth and also plaque.Plaque buildup on teeth is a result of the proliferation of oral microorganisms. Streptococcus mutans is responsible for bacterium in plaque production and caries progression.The common name for this gel concoction is "toothpaste."It has been shown that both betel leaf extract and gambier extract have antibacterial activity against Streptococcus mutans, however it is unknown whether or not the combination of the two extracts also has antibacterial activity against Streptococcus mutans. This research article mainly focused on combine substances in an effort to produce an antibacterial agent with synergistic properties that may be included into a gel for cleaning one's teeth.Twenty percent gambier and two percent betel extracts were utilized to make the gel. The combined inhibition zone is 3.09 mm, which is still sufficient for stop the growth and kill the bacteria.